Detection of antibiotics resistance genes in clinical isolates of Klebsiella pneumonia - W.Albassam, Wasan (Iraqi Journal of Science, 2023)
Total of 46 isolates of Klebsiella pneumoniae were collected from patients attending (Al-Yarmook Hospital and Education Labs / medical city), and isolates were re-identified, depending on morphology and biochemical tests . Disk diffusion method was employed to determine antibiotic susceptibility of forty six isolates by using eleven antibiotics .The results revealed the sensitivity of six isolates (9.3%) to Imipenem and Meropenem . On the other hand the isolates were showed 23.9% resistant against Ciprofloxacin, while some isolates shown higher resistant against several antimicrobial agents such as 65.2%, 69.0% for Amikacin and Cefepime consequently , 71.1%, 71.7 % for Amoxicillin -Clauvulanic acid and Gentamicin and 82.6% against Piperacillin , Nitrofurantoin and Ceftazidime. The isolates also appeared high level of resistance against Cefotaxime at a percentage 91.3% . Depending on the obtained results 6 isolates were selected assigned (K21, K32, K33, K37, K38, K43) for detection of blaTEM, blaSHV, blaKPC and AmpC because of its resistance of almost chosen antibiotics. The selected isolates were PCR-positive for blaTEM which showed bands in 209 pb., on the other hand the result revealed that the isolates K33,K32 posses encoding to blaSHV of 590pb in size,. In regard to blaKPC gene only K37 (16%)gave 811 pb . All selected isolate gave negative results to AmpC. The selected isolates were detected of beta-lactamase production by using acidimetric tests (tube method) , all isolates gave positive result.